Quitter : a memoir of drinking, relapse, and recovery - Barnett, Erica C. (Viking, 2020)
"With remarkably brave and vulnerable writing, Barnett expands on her personal story to confront the dire state of addiction in America, the rise of alcoholism in American women in the last century, and the lack of rehabilitation options available to addicts. At a time when opioid addiction is a national epidemic and one in twelve Americans suffers from alcohol abuse disorder, Quitter is essential reading for our age and an ultimately hopeful story of Barnett's own hard-fought path to sobriety"--